2014
DOI: 10.1007/978-3-642-39383-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Virasoro Central Charges for Nichols Algebras

Abstract: ABSTRACT. A Virasoro central charge can be associated with each Nichols algebra with diagonal braiding in a way that is invariant under the Weyl groupoid action. The central charge takes very suggestive values for some items in Heckenberger's list of rank-2 Nichols algebras. In particular, this might be viewed as an indication of the existence of reasonable logarithmic extensions of W 3 ≡ WA 2 , WB 2 , and WG 2 models of conformal field theory. In the W 3 case, the construction of an octuplet extended algebra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…From the lattice perspective, the corresponding W-extended CFTs WLM(p, p ′ ) are described [49][50][51] by the same LM(p, p ′ ) lattice models but with a special class of restricted boundary conditions which, in the continuum scaling limit, respect the W-extended symmetry. Construction of other cosets of logarithmic CFTs with Wsymmetry first appeared in [52,53], whereas the first hints of the existence of a W diagonal coset construction of the WLM(p, p ′ ) models, of an analogous form to (1.1), appeared in [54]. Specifically, it was found that the Grothendieck ring associated with W-projective representations leads to a Verlindelike formula involving coset graphs A…”
Section: Introductionmentioning
confidence: 99%
“…From the lattice perspective, the corresponding W-extended CFTs WLM(p, p ′ ) are described [49][50][51] by the same LM(p, p ′ ) lattice models but with a special class of restricted boundary conditions which, in the continuum scaling limit, respect the W-extended symmetry. Construction of other cosets of logarithmic CFTs with Wsymmetry first appeared in [52,53], whereas the first hints of the existence of a W diagonal coset construction of the WLM(p, p ′ ) models, of an analogous form to (1.1), appeared in [54]. Specifically, it was found that the Grothendieck ring associated with W-projective representations leads to a Verlindelike formula involving coset graphs A…”
Section: Introductionmentioning
confidence: 99%
“…Woronowicz, M. Rosso, S. Majid and G. Lusztig in many different ways, see for example [37,38,32,30,29]. Besides that, Nichols algebras have interesting applications to other research fields such as Kac-Moody Lie superalgebras [1,Example 3.2] and conformal field theory [34,35,36]. Nichols algebras appeared naturally in the classification of pointed Hopf algebras by the lifting method of N. Andruskiewitsch and H.-J.…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years, a lot of research has been devoted to understanding the so called logarithmic conformal field theories and related irrational vertex algebras [2,4,[18][19][20]24,30,32], etc. In these theories, modularity either holds with some modifications, as seen in C 2 -cofinite vertex operator algebras (VOAs), or is completely absent as is the case of non C 2 -cofinite VOAs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for Q = A 1 , W ( p) Q is precisely the (1, p)-singlet algebra discussed in [10,14]. Because of the integrality condition, the previous algebra can be maximally extended within the lattice vertex algebra leading to [2,12,18,32] …”
Section: Introductionmentioning
confidence: 99%